Microfinance and Entrepreneurial Growth among Marginalized Communities: A Step towards Inclusive Economic Development (International Journal of Food and Nutritional Sciences, 2022)
Microfinance serves as a powerful enabler of entrepreneurship among marginalized communities by expanding access to financial resources traditionally denied to them. Through small, collateral-free loans and supportive financial services, individuals from disadvantaged backgrounds—particularly women, rural poor, and socially excluded groups—are able to initiate and sustain micro-enterprises. Such entrepreneurial activity not only improves household income and self-reliance but also promotes broader goals of social equity and economic inclusion. While the impact of microfinance is widely recognized, sustainable progress depends on integrating financial services with skill development, market access, and institutional support. This study highlights the transformative potential of microfinance in fostering inclusive economic growth and reducing structural inequalities when implemented as part of a holistic development strategy